Antioxidant Capacity and Thermal Stability of Arthrospira platensis Extract Encapsulated in Starch Sodium Octenyl Succinate with Freeze-, Spray-, and Nanospray-Drying - Vesta Navikaitė-Šnipaitienė; Dovilė Liudvinavičiūtė; Ramunė Rutkaitė; Vaida Kitrytė-Syrpa; Michail Syrpas (Molecules)
Arthrospira platensis is a filamentous cyanobacterium produced commercially for human consumption, and it is a source of phycocyanin (PC), which recently stirred up great interest due to its anti-inflammatory, radical scavenging, antioxidant and hepato-protective properties. This work has studied the encapsulation of A. platensis extract in starch sodium octenyl succinate by employing freeze-drying and two spray-drying techniques, conventional and nanospray-drying. The main characteristics and properties, including PC encapsulation efficiency, size, colour, and thermal stability of the capsules, were evaluated. Moreover, the antioxidant capacity of encapsulated extract and release of PCs into saliva simulant, were studied and compared. Similar PC encapsulation efficiency was achieved using freeze-drying and nanospray-drying techniques with values of 67–71% and 70–78%, respectively. Meanwhile, the conventional spray-drying method achieved significantly lower encapsulation efficiency values (38–42%). The thermal stability of encapsulated A. platensis extract was improved as demonstrated by the higher decomposition temperature, which was increased by 8–11 °C, 11–15 °C, and 22–23 °C for spray-dried, nanospray-dried and freeze-dried samples, respectively. The nanospray-drying technique allowed the production of the smallest particles with an average diameter of 2–14 µm, good colour and thermal stability, and antioxidant capacity. Overall, the results demonstrated the potential of A. platensis extract encapsulation in modified starch using several techniques with potential application as bioactive ingredients in nutraceutical or pharmaceutical products.